2023
DOI: 10.7554/elife.81492
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian forelimb evolution is driven by uneven proximal-to-distal morphological diversity

Abstract: Vertebrate limb morphology often reflects the environment due to variation in locomotor requirements. However, proximal and distal limb segments may evolve differently from one another, reflecting an anatomical gradient of functional specialization that has been suggested to be impacted by the timing of development. Here we explore whether the temporal sequence of bone condensation predicts variation in the capacity of evolution to generate morphological diversity in proximal and distal forelimb segments acros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
0
5
1
Order By: Relevance
“…This may explain why, although carpometacarpus size is strongly relevant to flight-style across birds, its 3D shape– which might not be evolving under the same constraints– exhibits an even clearer relationship to external wing geometry and flight-style variety 33 , 49 . Our result here is distinct from observations in mammals 57 , in which forelimb evolution exhibits a strong proximo-distal gradient of morphological disparity. This departure in birds from a pattern reflecting the underlying embryogenetic sequence lends further credence to the hypothesis that integration within the avian wing may be under strong mechanical constraint that causes a unique variance structure and evolutionary coalescence around a small range of wing proportions.…”
Section: Discussioncontrasting
confidence: 99%
“…This may explain why, although carpometacarpus size is strongly relevant to flight-style across birds, its 3D shape– which might not be evolving under the same constraints– exhibits an even clearer relationship to external wing geometry and flight-style variety 33 , 49 . Our result here is distinct from observations in mammals 57 , in which forelimb evolution exhibits a strong proximo-distal gradient of morphological disparity. This departure in birds from a pattern reflecting the underlying embryogenetic sequence lends further credence to the hypothesis that integration within the avian wing may be under strong mechanical constraint that causes a unique variance structure and evolutionary coalescence around a small range of wing proportions.…”
Section: Discussioncontrasting
confidence: 99%
“…At the other extreme, body mass of the ruminants in tribe Antilopini are consistently overpredicted by metacarpus length with an average %PE of roughly −24%, as they have long, gracile extremities and tend to occur in open habitats (Table 4, Figure 3). These patterns provide an interesting platform on which to explore the functional associations between habitat and body mass in ungulates in the future, particularly through a developmental lens where proximal limb segments are more constrained in morphology relative to distal limb elements which may reflect functional variation related to locomotion and habitat (Rothier et al, 2023; Scott, 1985; Young, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The use of long bone lengths in fossil ruminant ecology may alternatively be found in reconstructing relationships with habitat, as Scott (1983Scott ( , 1985 suggested that distal limb proportions, in particular, may adapt more quickly to changes in substrate than 4, Figure 3). These patterns provide an interesting platform on which to explore the functional associations between habitat and body mass in ungulates in the future, particularly through a developmental lens where proximal limb segments are more constrained in morphology relative to distal limb elements which may reflect functional variation related to locomotion and habitat (Rothier et al, 2023;Scott, 1985;Young, 2013).…”
Section: Inferences From Long Bone Lengths and Circumferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This puts us back to a discussion about the origins of evolutionary novelty and its relatedness to anatomical (dis)integration (e.g., (Evans et al, 2021;Olson & Miller, 1958;Wagner & Altenberg, 1996;Wagner & Lynch, 2010;Zelditch & Goswami, 2021)). However, the evolutionary patterns observed in the humerus of cetaceans are not universal even across mammals (López-Aguirre et al, 2021;Rothier et al, 2023) and broadening the range of taxa to be examined, especially on the basalmost extinct forms and other deep lineages of aquatic mammals, seems beneficial for understanding the bigger picture which can be quite complex (Goswami et al, 2015;Lungmus & Angielczyk, 2021).…”
Section: Discussionmentioning
confidence: 99%